Single-cell RNA sequencing identifies senescent cerebromicrovascular endothelial cells in the aged mouse brain - Kiss, Tamas (GeroScience, 2020)
Age-related phenotypic changes of cerebromicrovascular endothelial cells lead to dysregulation of cerebral blood flow and blood-brain barrier disruption, promoting the pathogenesis of vascular cognitive impairment (VCI). In recent years, endothelial cell senescence has emerged as a potential mechanism contributing to microvascular pathologies opening the avenue to the therapeutic exploitation of senolytic drugs in preclinical studies. However, difficulties with the detection of senescent endothelial cells in wild type mouse models of aging hinder the assessment of the efficiency of senolytic treatments. To detect senescent endothelial cells in the aging mouse brain, we analyzed 4233 cells in fractions enriched for cerebromicrovascular endothelial cells and other cells associated with the neurovascular unit obtained from young (3-month-old) and aged (28-month-old) C57BL/6 mice. We define 13 transcriptomic cell types by deep, single-cell RNA sequencing. We match transcriptomic signatures of cellular senescence to endothelial cells identified on the basis of their gene expression profile. Our study demonstrates that with advanced aging, there is an increased ratio of senescent endothelial cells (~ 10%) in the mouse cerebral microcirculation. We propose that our single-cell RNA sequencing–based method can be adapted to study the effect of aging on senescence in various brain cell types as well as to evaluate the efficiency of various senolytic regimens in multiple tissues.